The fate of phosphorus in sediments after the full operation of the Three Gorges Reservoir, China. (July 2016) - Wu, Yanhong; Wang, Xiaoxiao; Zhou, Jun; Bing, Haijian; Sun, Hongyang; Wang, Jipeng
Abstract: The hydro-dynamic conditions have been changed after the impoundment of Three Gorges Reservoir (TGR), which result in changes of phosphorus (P) distribution in sediments. To investigate the variation and storage of P in the surface sediments of the TGR, continuously and intermittently submerged sediment samples were collected from 14 sites in 2014, and P fractions were analyzed using a modified Hedley sequential extraction method. The results showed that the concentrations of total P (TP) (904 ± 105 mg/kg) in the sediments did not exhibit an apparent spatial trend. A decreasing trend of bioavailable P (Bio-P) concentration in the continuously submerged sediment (177 ± 29 mg/kg) was observed from Fuling to Zigui, while an opposite trend appeared in the intermittently submerged sediment (139 ± 49 mg/kg) from Jiangjin to Zigui. The water depth and sediment grain size had important implications for the variation of the Bio-P in the sediments along the TGR. After the full operation of the TGR, the concentration of TP in the intermittently submerged sediment from Fengjie to Zigui was significantly higher in 2014 compared with that in 2009. The continuously submerged sediment is a major P pool of the TGR with an annual Bio-P deposition flux of 2.14 × 10 4 t/a, of which 87% was retained in the reaches from Fuling to Zigui. Considering the slow release of P from the sediment (0.16–2.75 t/a), the sediment has been a P "sink" since the full operation of the TGR in 2010. Graphical abstract: Highlights: The distribution of phosphorus is associated with the deposition of fine particles. The spatio-temporal distribution of phosphorus changed after the impoundment. Bioavailable phosphorus was mainly stored in the reaches from Fuling to Fengjie. Total phosphorus in the sediment from Fengjie to Zigui has increased since 2010. The sediment has been a phosphorus "sink" since the full impoundment of the TGR. Abstract : Spatial and temporal accumulations of phosphorus in the sediments have been observed after the full impoundment of the Three Gorges Reservoir in 2010.